2011
DOI: 10.1371/journal.pone.0023006
|View full text |Cite
|
Sign up to set email alerts
|

Seedling Stage Strategies as a Means of Habitat Specialization in Herbaceous Plants

Abstract: The regeneration niche has been little investigated in studies of community assembly and plant distribution. We examined adaptive associations between seedling traits and habitat specialization. Two habitat contrasts were investigated across several evolutionary lineages of angiosperms: species specialized to forest vs. open habitats and to dry vs. wet habitats. We also tested whether effects of shade and drought vary independently or, alternatively, if shade may amplify effects on drought-stressed plants. See… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(47 reference statements)
0
3
1
Order By: Relevance
“…5). Our findings are not incompatible with studies showing forest species to have adaptive traits in the seedling or adult phase to survive in shaded habitats, such as shade avoidance or shade tolerance syndromes (Henry and Aarssen, 1997;ten Brink and Bruun, 2011). It remains, however, to be investigated to what degree germination strategy and attributes of the established phase, such as shade tolerance, are coevolved (Silvertown, 1981).…”
Section: Discussioncontrasting
confidence: 70%
“…5). Our findings are not incompatible with studies showing forest species to have adaptive traits in the seedling or adult phase to survive in shaded habitats, such as shade avoidance or shade tolerance syndromes (Henry and Aarssen, 1997;ten Brink and Bruun, 2011). It remains, however, to be investigated to what degree germination strategy and attributes of the established phase, such as shade tolerance, are coevolved (Silvertown, 1981).…”
Section: Discussioncontrasting
confidence: 70%
“…These interact with microclimatic conditions to determine plant growth, by affecting the photosynthetic capacity to use light and altering herbivory and microbial activity (Valladares, 2003). Consequently, light and temperature conditions vary according to habitat conditions, thus driving germination and seedling establishment strategies (ten Brink & Bruun, 2011). Shrubs grow under many different forest canopy densities, and face wide variations in microclimate according to the forest type/canopy composition.…”
Section: Introductionmentioning
confidence: 99%
“…The most often cited negative effects of native species on invasives are caused by competition (Levine et al ., ). Although competition from resident species takes place at all plant life‐cycle stages (ten Brink & Bruun, ), the vast majority of studies have studied adult plant biomass or fecundity as response variables (Leger & Espeland, ). However, factors affecting seed germination and recruitment also have the potential to affect plant demography and long‐term survival of populations (Tielbörger & Prasse, ; Orrock & Christopher, ; ten Brink & Bruun, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although competition from resident species takes place at all plant life‐cycle stages (ten Brink & Bruun, ), the vast majority of studies have studied adult plant biomass or fecundity as response variables (Leger & Espeland, ). However, factors affecting seed germination and recruitment also have the potential to affect plant demography and long‐term survival of populations (Tielbörger & Prasse, ; Orrock & Christopher, ; ten Brink & Bruun, ). It has been reported that germination and initial root and shoot development may be particularly sensitive to competition (Foster & Gross, ).…”
Section: Introductionmentioning
confidence: 99%